Time-Averaged Heat Transfer and Vortex Shedding of a Singular and Twin Heated Bluff Bodies in Cross Flow - Etminan, A.; Sharifian, A.; Reda, E.; Harun, Z. (International Journal of Engineering and Technology, 2018)
Flow characteristics in the onset of vortex shedding and heat transfer pattern over a single and two same-sized square prisms placed in tandem are studied numerically. All simulations are carried out for Reynolds numbers range varying from 1 to 200 and spacing between the prisms in the order of five widths of prism for in tandem configuration. The calculations are done employing a finite volume in-house computer program according to semi-implicit method for pressure linked equations-consistent (SIMPLEC) numerical procedure and non-staggered mesh in 2-dimensional, steady/unsteady and incompressible flow regimes. The instantaneous and time-averaged streamlines as well as iso-therm pattern for different Reynolds numbers are analysed. Furthermore, the influence of Reynolds number and the onset of vortex shedding on the flow pattern are studied in detail. Three distinct patterns namely fully-attached, trailing-edge separation and leading-edge separation were observed.Â Â